CHOOSING THE OPTIMAL TREATMENT METHOD TAKING INTO ACCOUNT THE NATURE OF INFLAMMATORY CHANGES IN THE DENTAL PULP - Aliyev, B.F. (World of Medicine and Biology, 2022)
This study presents the results of determining the optimal method of treating pulpitis, depending on the nature of inflammatory changes in the dental pulp. For this purpose, 115 people with various pulpitis were under observation. The diagnosis was carried out according to the classification adopted by WHO in 1997 – K04 Diseases of pulp and periapical tissues, according to which the examined were divided into three groups. In group I of 40 patients, the biological method carried out the treatment. In group II, 35 patients underwent pulpotomy; in group III, 40 patients underwent pulpectomy. The results of a 2-year follow-up in groups of patients showed that pulpectomy was successful in 80.0 % of cases and unsuccessful in 20.0 %. In this group of patients, the PAI index after 2 years was 1.10±0.5 points. In the biological treatment group, 75.0 % of cases were successful, and only 25.0 % experienced complications. 2 years after treatment in periapical tissues, PAI was 1.13±0.64 points. In the group of patients where pulpotomy was used, the treatment was successful in 37.1 % of cases and complications were noted in 62.9 % of cases. Modified PAI totaled 1.17±0.73 points. The study showed that in the treatment of patients with pulpitis, depending on the prevalence of the inflammatory process in the dental pulp, pulpectomy and the biological method of treatment turned out to be the most effective and reliable.